Left bundle branch area pacing delivery of cardiac resynchronization therapy and comparison with biventricular pacing. (13th May 2020) - Li, Xiaofei; Qiu, Chunguang; Xie, Ruiqin; Ma, Wentao; Wang, Zhao; Li, Hui; Wang, Hao; Hua, Wei; Zhang, Shu; Yao, Yan; Fan, Xiaohan
Abstract: Aims: This multicentre observational study aimed to prospectively assess the efficacy of left bundle branch area pacing (LBBAP) in heart failure patients with left bundle branch block (LBBB) and compare the 6‐month outcomes between LBBAP and biventricular pacing (BVP). Methods and results: Consecutive patients with LBBB and left ventricular ejection fraction (LVEF) ≤ 35% were prospectively recruited if they had undergone LBBAP as a primary or rescue strategy from three separate centres from March to December 2018. Patients who received BVP in 2018 were retrospectively selected by using 2 to 1 propensity score matching to minimize bias. Implant characteristics and echocardiographic parameters were assessed during the 6‐month follow‐up. LBBAP procedure succeeded in 81.1% (30/37) of patients, with selective LBBAP in 10 patients, and 3 of 20 patients combined non‐selective LBBAP and LV lead pacing for further QRS narrowing. LBBAP resulted in significant QRS narrowing (from 178.2 ± 18.8 to 121.8 ± 10.8 ms, P < 0.001, paced QRS duration ≤ 130 ms in 27 patients) and improved LVEF (from 28.8 ± 4.5% to 44.3 ± 8.7%, P < 0.001) during the 6‐month follow‐up. The comparison between 27 patients with LBBAP alone and 54 of 130 matching patients with BVP showed that LBBAP delivered a greater reduction in the QRSd (58.0 vs. 12.5 ms, P < 0.001), a greater increase in LVEF (15.6% vs. 7.0%, P < 0.001), and greater echocardiographic (88.9% vs. 66.7%, P = 0.035) and super response (44.4% vs. 16.7%, P = 0.007) to cardiac resynchronization therapy. Conclusions: LBBAP could deliver cardiac resynchronization therapy in most patients with heart failure and LBBB, and might be a promising alternative resynchronization approach to BVP.